2021
DOI: 10.1055/s-0041-1728718
|View full text |Cite
|
Sign up to set email alerts
|

Tone Burst Masseter Vestibular Evoked Myogenic Potentials: Normative Values and Test–Retest Reliability

Abstract: Background Masseter vestibular evoked myogenic potential (mVEMP) is a recent tool for the assessment of vestibular and trigeminal pathways. Though a few studies have recorded mVEMP using click stimuli, there are no reports of these potentials using the more conventional VEMP eliciting stimuli, the tone bursts. Purpose The aim of the study is to establish normative values and determine the test–retest reliability of tone burst evoked mVEMP. Research Design The research design type is normati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 31 publications
4
27
1
Order By: Relevance
“…Further, no significant differences were found in peak latencies, EMGscaled and unscaled peak to peak amplitudes, and IAAR across ears and genders for both mVEMP and cVEMP responses. This finding aligns with previous studies which have also indicated the absence of ear and gender influences in mVEMPs (Vignesh et al 22 ; Basoz et al 27 ) and cVEMPs (Akin et al 5 ). The study revealed a relatively higher degree of variability in EMG unscaled peak-to-peak amplitude.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Further, no significant differences were found in peak latencies, EMGscaled and unscaled peak to peak amplitudes, and IAAR across ears and genders for both mVEMP and cVEMP responses. This finding aligns with previous studies which have also indicated the absence of ear and gender influences in mVEMPs (Vignesh et al 22 ; Basoz et al 27 ) and cVEMPs (Akin et al 5 ). The study revealed a relatively higher degree of variability in EMG unscaled peak-to-peak amplitude.…”
Section: Discussionsupporting
confidence: 93%
“…In the study, 100% of the participants had 500 Hz tone burst-evoked mVEMP and cVEMP response parameters. Similar findings have been reported previously for mVEMPs (Vignesh et al 22 ; Vinayagar et al 23 ; Neupane et al 24 )…”
Section: Discussionsupporting
confidence: 92%
“…In our study, while absolute latency values in the control group were not significantly different in bilateral stimulation compared to unilateral stimulation (p=0.05), they were found to be significantly higher in the experimental group (p<0.001). Vignesh et al (2021), when looking at the latency values of the total ears in the individuals, the p1 latency was found to be 12.88, while our study was found to be 13.02.…”
Section: Accepted Manuscriptcontrasting
confidence: 56%
“…In the same study, while N1 lattans were 21.18, our study was 18.88 15 . It is thought that this difference may be due to Vignesh's use of tone burst stimulus and our use of click stimulus.…”
Section: Accepted Manuscriptmentioning
confidence: 49%
“…Vanspauwen et al compared the ICC for N1 and P1 between the standard electrode montage and a modified belly tendon montage derived from Sandhu et al, revealing higher ICC for the clinical standard (35,36). Even with newly adapted electrode montages or oVEMP stimuli, values of ICC for the clinical standard remained on the level of previous studies while the two newly introduced electrode montages N and L showed higher levels of reliability (15,36,54). Vanspauwen explains the rather low values of ICC for latencies in the context of the ICC's calculation method and the small size of the dataset.…”
Section: Reliability Of Ovemp Measurements Compared Withmentioning
confidence: 96%